Monoclonal antibodies protect aged rhesus macaques from SARS-CoV-2-induced immune activation and neuroinflammation - Anil Verma (Elsevier, 2021)
Summary: Anti-viral monoclonal antibody (mAb) treatments may provide immediate but short-term immunity from coronavirus disease 2019 (COVID-19) in high-risk populations, such as people with diabetes and the elderly; however, data on their efficacy in these populations are limited. We demonstrate that prophylactic mAb treatment blocks viral replication in both the upper and lower respiratory tracts in aged, type 2 diabetic rhesus macaques. mAb infusion dramatically curtails severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-mediated stimulation of interferon-induced chemokines and T cell activation, significantly reducing development of interstitial pneumonia. Furthermore, mAb infusion significantly dampens the greater than 3-fold increase in SARS-CoV-2-induced effector CD4 T cell influx into the cerebrospinal fluid. Our data show that neutralizing mAbs administered preventatively to high-risk populations may mitigate the adverse inflammatory consequences of SARS-CoV-2 exposure.